The Americans United States history since 1877 - Teja, Jesús F. de la; Garnier, Vaerie; Green, Kerry; Harman, Kristin; Shaw-Kelly, Aderienne; Danzer, Gerald A. (Houghton Mifflin Harcourt, 2016)
Exploration and the colonial era, beginnings to 1763 -- Revolution and the early republic, 1763-1800 -- The growth of a young nation, 1800-1850 -- The union in peril, 1850-1877 -- Changes on the western frontier, 1877-1900 -- A new industrial age, 1877-1900 -- Immigrants and urbanization, 1877-1914 -- Life at the turn of the 20th century, 1877-1917 -- The progressive era, 1890-1920 -- America claims an empire, 1890-1920 -- The First World War, 1914-1920 -- Politics of the Roaring Twenties, 1919-1929 -- The roaring life of the 1920s, 1920-1929 -- The Great Depression begins, 1929-1933 -- The New Deal, 1933-1940 -- World war looms, 1931-1941 -- The United States in World War II, 1941-1945 -- Cold War conflicts, 1945-1960 -- The postwar boom, 1946-1960 -- The new frontier and the great society, 1960-1968 -- Civil rights, 1954-1968 -- The Vietnam War years, 1954-1975 -- An era of social change, 1960-1975 -- An age of limits, 1968-1980 -- The conservative tide, 1980-1992 -- The United States in today's world, 1992-present -- Issues in the 21st century -- Atlas -- Facts about the states -- Presidents of the United States -- Glossary -- Spanish glossary